CHALLENGES OF THE EUROPEAN UNION BUDGET REFORM - ELENA PADUREAN; EMILIA CAMPEANU; ANDREEA STOIAN (Challenges of the Knowledge Society)
At the European Union are presented some concerns regarding the need to review its policies starting with the recommendations for the budget reform and the change of the EU basic policies. Therefore, it was discussed some scenarios that involve the enlargement of the EU. However, the economic context imposes some constraint regarding this process to accept Croatia and Turkey as EU members. The aim of this paper is to present these scenarios. Taking into consideration that the empirical investigation of these scenarios are difficult to achieve based on short time series data, we propose a new set of analyze based on important macroeconomic indicators.